Again 1907?: Korean Revivalism’s Nostalgic Futures - Im, Bo kyung Blenda (Liturgy, 2025)
This article examines how nostalgia, revival, and liturgical song shape Christian subjectivity. Through analysis of YWAM Korea’s Puhŭng: Revival (1997) album, historicization of Korean Protestant affinity for the 1907 Pyongyang Great Revival, and engagement with affect theory, the author elucidates the ways in which nostalgic revival in Korean Christianity orients worshipers’ political desires around the singular futurity of North-South reunification. As such, this article prompts a consideration of liturgical leaders’ responsibilities to steward memory and historical narrative in relation to global capitalism’s emotional infrastructures.